NEW NATIONALITY PROVISIONS AND THEIR IMPACT ON INTERNATIONAL PERSONAL STATUS RULES - Assist. Legal Consultant Sarah Hassan Alwan; Prof. Dr. Iyad Mutashar Sayhoud (Scholar Express Journals, 2023)
Articles 19-24 of the Iraqi Civil Code No. 40 of 1951 regulate the subject of conflict of laws rules in personal situations, which refer to the individual's personal law, namely the Nationality Act, if the nationality of women and men is of equal legal value under the Iraqi Constitution in force for the year 2005. (18/2), article (3/1) of the Iraqi Nationality Law in force No. 26 of 2006, and Act No. (33) In 2011, the Act lifting the reservation of the Federal Republic of Iraq to Article IX of the CEDAW Convention requires a review of these articles of the Civil Code in order to achieve the practical equality of the principle of the conceptual equality of women's nationality with men. Perhaps the question here is whether such an amendment can be achieved, assessed and effected, which has created a major problem through the extent to which such an amendment is opposed to the provisions of the Islamic Shari 'a in terms of the reliance of the Personal Status Law on the rules of the Islamic Shari'a
Keywords: Nationality rulings; personal status conflict; the principle of equality; Islamic law